Security in the twenty first century : a Bangladesh perspective - Osmany, Mufleh R.; Ahmad, Muzaffer; Bangladesh Institute of International and Strategic Studies (Dhaka : Academic Press and Publishers in association with Bangladesh Institute of International and Strategic Studies, 2003)
Contributed articles.
"Published on the occasion of BIISS silver jubilee"--T.p. verso.
Includes bibliographical references.
Keywords: National security -- Bangladesh; Sea-power -- Bangladesh